Analysis of Pre-service Teachers' Skills in Providing Feedback to Students During Field Experience Practice in School - Hardianto Rahman; Muhammad Irfan; Faidah Yusuf; A. Muh. Ali; A. Umar Abadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study investigates pre-service teachers' (PST) feedback skills during Field Experience Practice (FEP), identifies influencing factors, and examines their impact on student learning. Method: A mixed-methods approach was used, combining quantitative data from 42 PSTs and 57 teachers via questionnaires and qualitative insights from interviews, observations, and documentation. Descriptive statistics were employed to categorize feedback proficiency, while qualitative analysis explored contextual influences. Results: Findings reveal three levels of feedback skills—high, medium, and low—determined by internal factors (pedagogical understanding, teaching experience) and external factors (supervisor support, school environment). Effective feedback enhances student comprehension, motivation, and engagement, yet many PSTs struggle with providing structured, actionable feedback. Novelty: This study uniquely focuses on PSTs’ feedback skills during FEP, highlighting key factors influencing their effectiveness and the impact on student learning. It also provides evidence-based recommendations for strengthening teacher education curricula by integrating structured feedback training, ultimately improving classroom interactions and learning outcomes.